RanBP3 Regulates Proliferation, Apoptosis and Chemosensitivity of Chronic Myeloid Leukemia Cells via Mediating SMAD2/3 and ERK1/2 Nuclear Transport - Li, Qian; Huang, Zhenglan; Peng, Yuhang; Wang, Xin; Jiang, Guoyun; Wang, Teng; Mou, Ke; Feng, Wenli (Frontiers in Oncology, 2021)
Abnormal subcellular localization of proteins is an important cause of tumorigenesis and drug resistance. Chromosome region maintenance 1 (CRM1), the nuclear export regulator of most proteins, has been confirmed to be over-expressed in various malignancies and is regarded as an efficient target. But the potential role of the CRM1 cofactor RanBP3 (Ran Binding Protein 3) is left unrevealed in chronic myeloid leukemia (CML). Here, we first detected the level of RanBP3 in CML and found an elevated RanBP3 expression in CML compared with control. Then we used shRNA lentivirus to down-regulated RanBP3 in imatinib sensitive K562 cells and resistant K562/G01 cells and found RanBP3 silencing inhibited cell proliferation by up-regulating p21, induced caspase3-related cell apoptosis, and enhanced the drug sensitivity of IM in vitro. Notably, we observed that RanBP3 silencing restored imatinib sensitivity of K562 cells in NOD/SCID mice. Mechanistically, the nuclear aggregation of SMAD2/3 revealed that tumor suppressor axis (TGF-β)-SMAD2/3-p21 was the anti-proliferation program related to RanBP3 knockdown, and the decrease of cytoplasmic ERK1/2 caused by RanBP3 interference leaded to the down-regulation of anti-apoptosis protein p(Ser112)-BAD, which was the mechanism of increased cell apoptosis and enhanced chemosensitivity to imatinib in CML. In summary, this study revealed the expression and potential role of RanBP3 in CML, suggesting that targeting RanBP3 alone or combined with TKIs could improve the clinical response of CML.